Role and benefits of infectious diseases specialists in the COVID-19 pandemic: multilevel analysis of care provision in German hospitals using data from the Lean European Open Survey on SARS-CoV-2 infected patients (LEOSS) cohort - Tscharntke, Lene T.; Jung, Norma; Hanses, Frank; Koll, Carolin E. M.; Pilgram, Lisa; Rieg, Siegbert; Borgmann, Stefan; de Miranda, Susana M. Nunes; Scherer, Margarete; Spinner, Christoph D.; Rüthrich, Maria; Vehreschild, Maria J. G. T.; et al. (Infection, 2025)
This study investigates the care provision and the role of infectious disease (ID) specialists during the coronavirus disease-2019 (COVID-19) pandemic.